Tissue Pharmacokinetic Properties and Bystander Potential of Hypoxia-Activated Prodrug CP-506 by Agent-Based Modelling - Jackson-Patel, Victoria; Liu, Emily; Bull, Matthew R.; Ashoorzadeh, Amir; Bogle, Gib; Wolfram, Anna; Hicks, Kevin O.; Smaill, Jeff B.; Patterson, Adam V. (Frontiers in Pharmacology, 2022)
Hypoxia-activated prodrugs are bioactivated in oxygen-deficient tumour regions and represent a novel strategy to exploit this pharmacological sanctuary for therapeutic gain. The approach relies on the selective metabolism of the prodrug under pathological hypoxia to generate active metabolites with the potential to diffuse throughout the tumour microenvironment and potentiate cell killing by means of a ‘bystander effect’. In the present study, we investigate the pharmacological properties of the nitrogen mustard prodrug CP-506 in tumour tissues using in silico spatially-resolved pharmacokinetic/pharmacodynamic (SR-PK/PD) modelling. The approach employs a number of experimental model systems to define parameters for the cellular uptake, metabolism and diffusion of both the prodrug and its metabolites. The model predicts rapid uptake of CP-506 to high intracellular concentrations with its long plasma half-life driving tissue diffusion to a penetration depth of 190 µm, deep within hypoxic activating regions. While bioreductive metabolism is restricted to regions of severe pathological hypoxia (< 1 µM O2), its active metabolites show substantial bystander potential with release from the cell of origin into the extracellular space. Model predictions of bystander efficiency were validated using spheroid co-cultures, where the clonogenic killing of metabolically defective ‘target’ cells increased with the proportion of metabolically competent ‘activator’ cells. Our simulations predict a striking bystander efficiency at tissue-like densities with the bis-chloro-mustard amine metabolite (CP-506M-Cl2) identified as a major diffusible metabolite. Overall, this study shows that CP-506 has favourable pharmacological properties in tumour tissue and supports its ongoing development for use in the treatment of patients with advanced solid malignancies.